Quantitative Structure–Property Relationship Study to Predict Speed of Sound in Diverse Organic Solvents from Solvent Structural Information - Hemmateenejad, Bahram; Ilani-kashkouli, Poorandokht (Industrial & engineering chemistry research, 2012)
The interaction of solvents with ultrasonic waves is of drastic importance and has been the subject of many studies in recent years. In this study, the effect of solvent structural parameters on the speed of sound in chemical solvents was investigated through a quantitative structure–property relationship (QSPR). Genetic algorithm–multiple linear regression (GA-MLR) analysis was employed to select the most relevant subset of descriptors and, then, to develop the model. The validity of the obtained 10-parameter model was assessed by most widely used validation techniques. The predictive power of the model was evaluated by use of an external data set. The high level of accuracy of results approved the model. According to the model, those solvents that have stronger solvent–solvent interactions can create a more appropriate medium for passing and propagating sound waves and will result in higher speed of sounds.